2011
DOI: 10.1186/1742-6405-8-41
|View full text |Cite
|
Sign up to set email alerts
|

The antiretroviral efficacy of highly active antiretroviral therapy and plasma nevirapine concentrations in HIV-TB co-infected Indian patients receiving rifampicin based antituberculosis treatment

Abstract: BackgroundRifampicin reduces the plasma concentrations of nevirapine in human immunodeficiency virus (HIV) and tuberculosis (TB) co-infected patients, who are administered these drugs concomitantly. We conducted a prospective interventional study to assess the efficacy of nevirapine-containing highly active antiretroviral treatment (HAART) when co-administered with rifampicin-containing antituberculosis treatment (ATT) and also measured plasma nevirapine concentrations in patients receiving such a nevirapine-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The daily dosing of efavirenz and its coformulation with tenofovir and emtricitabine into a oncedaily pill (Atripla, Bristol-Myers Squibb, New York, NY) is also an important tool to enhance adherence given the already high pill count of anti-TB therapy. Rifampin causes a greater reduction of nevirapine levels than efavirenz levels, [98][99][100][101] but it is unclear if this results in more HIV virological failure, 99,[102][103][104] making nevirapine an acceptable alternative when efavirenz is unavailable (►Table 1).…”
Section: Treatment Of Hiv/aids In Persons With Tuberculosismentioning
confidence: 99%
“…The daily dosing of efavirenz and its coformulation with tenofovir and emtricitabine into a oncedaily pill (Atripla, Bristol-Myers Squibb, New York, NY) is also an important tool to enhance adherence given the already high pill count of anti-TB therapy. Rifampin causes a greater reduction of nevirapine levels than efavirenz levels, [98][99][100][101] but it is unclear if this results in more HIV virological failure, 99,[102][103][104] making nevirapine an acceptable alternative when efavirenz is unavailable (►Table 1).…”
Section: Treatment Of Hiv/aids In Persons With Tuberculosismentioning
confidence: 99%
“…In this study, when the mean increases in CD4 cells count were compared the difference was not significant for both groups of PLWHs in contrary to what had been reported as starting ART, particularly early during TB treatment, could jeopardize adherence to treatment and hence worsening of the immune response [ 20 ]. Hung et al [ 10 ], Sharma and colleagues [ 21 ], Sinha et al [ 12 ] and Lipman et al [ 11 ] also showed similar findings. According to one study the additional increment in CD4 count in patients with co-infection following treatment suggest that CD4 suppression at the onset of TB may be the direct result of mycobacterium growth and inflammation as well as interaction between TB and HIV in addition to the effect of HIV alone [ 21 ].…”
Section: Discussionmentioning
confidence: 57%
“…However, there are limited literatures which compared outcomes of ART in adult people living with HIV who are TB co-infected with that of PLWH without TB co-infection. Amongst those few literatures available, majority of them are from developed countries [ 10 12 ] and published works on this issue in resource poor setting like Ethiopia is scarce [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 Both adult and paediatric studies done in Africa, Thailand and India have shown varying levels of the effect on NVP plasma levels as a result of the drug-drug interaction during concomitant use of a rifampicin containing anti-TB regimen and a NVP based ART regimen. [4][5][6]8,[20][21][22][23] An intensive pharmacokinetic study of standarddose NVP with and without rifampicin in South African adults found sub-therapeutic NVP levels in 6 of 16 patients during rifampicin dosing. 8 A pharmacokinetic sub analysis conducted on 20 of the children in this study as reported by Barlow Mosha et al also found that NVP trough concentration was significantly reduced in children who received rifampicin and NVP concurrently.…”
Section: Discussionmentioning
confidence: 99%